Affect of political and economic instruments applicable in international trade - Hramova, Jeļena (Riga Graduate School of Law, 2019)
This paper addresses how political and economic tools are used by states when implementing trading policies and practices on both levels, on a regional level further moving to the international level. The main purpose of this paper is to determine how much politics is engaged when the states are shaping their foreign trade relations and whether the codes of conduct are distinctly reallocated between all players of the international trade. The cases mentioned in the paper give an overview on how the political tools are used by the traditionally dominant powers when it comes down to dispute settlements.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::International law; International trade